A Miniaturised Dual-Band Modified U-Shaped Monopole Antenna for 5G, Wi-Fi/WLAN/WiMAX and Ultra-Wideband Applications - Ansah, John Nyamekye (Faculty of Engineering, Universitas Tanjungpura, 2025)
This paper presents a miniaturised dual-band modified U-shaped monopole antenna for 5G, Wi-Fi/WLAN/WiMAX and ultra-wideband (UWB) applications. The antenna is designed and optimised using computer simulation technology (CST) microwave studio (MWS) suite version 2019. It features a circular patch modified into a U-shape by introducing geometrical slots, which significantly contribute to achieving wide bandwidth. The patch is mounted on an FR-4 substrate with a 1.6 mm thickness and a 4.3 relative permittivity value. The antenna has an area of 50 Ã— 50 and resonates at 2.45 GHz and 5.25 GHz, achieving return losses of -28.677 dB and -36.851 dB, with VSWR values of 1.0765 and 1.0292 at the respective operating frequencies. The corresponding gains are 2.282 dBi and 4.334 dBi, with directivity of 2.710 dBi and 5.206 dBi. It offers a huge impedance bandwidth of 7.564 GHz, effectively covering 2.0535-3.8333 GHz and 4.2158-10 GHz, which meet the operational requirements for 5G, Wi-Fi/WLAN/WiMAX and UWB applications. Additionally, the antenna measures 90.61% and 81.80% radiation efficiencies and 90.49% and 81.78% total efficiencies at the respective operating frequencies. The fractional bandwidths are 60.5% and 81.4% at 2.45 GHz and 5.25 GHz, respectively. Furthermore, the antenna exhibits an omnidirectional radiation pattern that demonstrates exceptional potential as a competitive solution for 5G, Wi-Fi/WLAN/WiMAX and UWB applications.